Fresno County Women Lawyers Annual Dinner: Honoring Mary Louise Frampton - Watkins, Howard::::::::: (1989)
Retired Judge Harold Thompson, Justice Hollis Best, 2nd District Court of Appeal Presiding Justice Arleigh Woods, retired Justice George Brown and Justice Pauline Davis Hanson